A COMPARATIVE STUDIES ON THE POPULATION DYNAMIC AND SURVIVAL OF GREEN LEAF HOPPER AND ZIGZAG LEAF HOPPER TRANSMITTING RICE TUNGRO VIRUS IN WEST BENGAL - MD. ALI AZGAR AND TAPAS KUMAR HEMBRAM (The Bioscan, 2018)
A study to find out the population dynamic and survival characteristics of both the rice tungro vectors, Green Leafhopper (GLH), Nephotettix virescens and Zigzag Leafhopper (ZLH), Recilia dorsalis was undertaken during 2015-16 at Regional Research Station (OAZ), UBKV, Majhian, Dakshin Dinajpur West Bengal. Result revealed that average population (average of 10 sweeps) of ZLH was high at the early stage during the month of June (4.5/ sweep) and July (12.5/sweep) compare to GLH population which was found to increase from the month of June (11.5/sweep) and reached its peak in October (38.8/sweep). But in general GLH population was high as compare to ZLH and a highest population (25.4 -28.5/sweep) of GLH was found at maximum tillering stage irrespective of varieties followed by flowering stage (16.5 -21.6), panicle initiation stage (13.5 - 18.4/sweep) and seedbed (2.6 -8.4/weep). Both GLH and ZLH were found in rice as well as in weed host but the GLH population was high in rice (4.2-8.6/sweep) and low in weed host (0.14-2.2/sweep) whereas ZLH population was high in weed (2.8-5.3/ sweep) and low in rice (2.7-3.2/sweep). It was also found that the survival period of GLH in rice varieties was high (8-21 days) compare to ZLH (6-18 days).